Applicacao Da Algebra A Geometria Licoes Coordenadas para Uso Dos Alumnos da Eschola Polytechnica (Lisboa na Imprensa Nacional., 1847)
Keywords: 10.Cover Damage; 18.Bookworm (Only Cover); 2.Damage; Condition: Poor; Hard Cover; Science Study and teaching

A Virgem da Polonia - Bastos, Jose Joaquim Rodrigues (Na Impresa Nacional, 1847)
Stamp of St. Joseph Seminary

M.T. Ciceronis De Oratore. Libri 3 - Cicero, Marcus Tullius (Lecoffre, 1847)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Hard Cover; Latinsk litteratur; Philosophy

Encyclopedie Catholique - Glaire, M. L'abbe (1847)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Encyclopedie Catholique - Glaire, M. L'abbe (1847)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Encyclopedie Catholique - Glaire, M. L'abbe (1847)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Encyclopedie Catholique - Glaire, M. L'abbe (1847)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Histoire de la vie et de l'episcopat de S. Charles Borromee - Martin, Alexandre (Mellier Freres, Libraires, 1847)